2012
DOI: 10.1186/1472-6947-12-135
|View full text |Cite
|
Sign up to set email alerts
|

Motivating medical information system performance by system quality, service quality, and job satisfaction for evidence-based practice

Abstract: BackgroundNo previous studies have addressed the integrated relationships among system quality, service quality, job satisfaction, and system performance; this study attempts to bridge such a gap with evidence-based practice study.MethodsThe convenience sampling method was applied to the information system users of three hospitals in southern Taiwan. A total of 500 copies of questionnaires were distributed, and 283 returned copies were valid, suggesting a valid response rate of 56.6%. SPSS 17.0 and AMOS 17.0 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 49 publications
2
52
0
12
Order By: Relevance
“…Furthermore, previous studies (e.g., DeLone & McLean, 2016;Shagari et al 2015) suggested that a positive relationship was present between system quality and AIS. Consistent with this, empirical findings have found a positive relationship between system quality and IS effectiveness (Chang et al, 2012;Hein et al, 2014;Hyung & Jae, 2010;Quintero, Pedroche, & Ramos, 2009;Shatat et al, 2013;Xu et al, 2013). Based on previous studies, examining system quality construct in the context of Nigerian banks is important specifically where there is persistent complaints of the system failures, system instability, fraud, and security issues (Dandago & Rufai, 2014;Ekwueme et al, 2012).…”
Section: System Qualitymentioning
confidence: 87%
See 4 more Smart Citations
“…Furthermore, previous studies (e.g., DeLone & McLean, 2016;Shagari et al 2015) suggested that a positive relationship was present between system quality and AIS. Consistent with this, empirical findings have found a positive relationship between system quality and IS effectiveness (Chang et al, 2012;Hein et al, 2014;Hyung & Jae, 2010;Quintero, Pedroche, & Ramos, 2009;Shatat et al, 2013;Xu et al, 2013). Based on previous studies, examining system quality construct in the context of Nigerian banks is important specifically where there is persistent complaints of the system failures, system instability, fraud, and security issues (Dandago & Rufai, 2014;Ekwueme et al, 2012).…”
Section: System Qualitymentioning
confidence: 87%
“…This study operationalized the construct as a second-order formative construct and measure with three first-order dimensions: 1) accuracy, 2) timeliness, and 3) completeness, which are all adapted from Chang, Chen, and Lan (2012). Accuracy is concerned with the correctness of the output produced by the system.…”
Section: Information Qualitymentioning
confidence: 99%
See 3 more Smart Citations